2020
DOI: 10.1007/s12178-020-09621-3
|View full text |Cite
|
Sign up to set email alerts
|

State of the Union on Ulnar Collateral Ligament Reconstruction in 2020: Indications, Techniques, and Outcomes

Abstract: Purpose of Review There has been a marked increase in the number of ulnar collateral ligament reconstructions performed annually and an associated increase in the amount of recent literature published. It is paramount that surgeons remain up to date on the current literature, as modern indications and surgical techniques continue to improve clinical outcomes. Recent Findings Our understanding of ulnar collateral ligament (UCL) injuries, treatment indications, and surgical techniques for UCL reconstruction cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 106 publications
(173 reference statements)
0
3
0
Order By: Relevance
“…Three such case series have been discussed at length in other review articles. 2 , 18 , 31 , 36 In short, Podesta et al found that among 34 athletes with symptomatic partial-thickness UCL tears, 88% treated with one PRP injection and a graded rehabilitation program returned to competition at an average time of 12 weeks. The study also reported significantly improved ultrasonographic medial joint space measurements and subjective questionnaire scores at follow-up.…”
Section: Biologic Augmentation Of Elbow Injurymentioning
confidence: 99%
“…Three such case series have been discussed at length in other review articles. 2 , 18 , 31 , 36 In short, Podesta et al found that among 34 athletes with symptomatic partial-thickness UCL tears, 88% treated with one PRP injection and a graded rehabilitation program returned to competition at an average time of 12 weeks. The study also reported significantly improved ultrasonographic medial joint space measurements and subjective questionnaire scores at follow-up.…”
Section: Biologic Augmentation Of Elbow Injurymentioning
confidence: 99%
“…Ulnar collateral ligament (UCL) injuries of the elbow are most often a result of intense valgus forces placed on the elbow and frequently occur in young overhead athletes. 1 , 2 Injury occurs during late cocking and acceleration phases of throwing in such athletes as baseball pitchers. 1 The first reconstruction technique, performed by Dr. Frank Jobe, was made famous by notable Major League Baseball player Tommy John, who underwent the original “Tommy John” procedure to reconstruct his UCL in 1974.…”
mentioning
confidence: 99%
“… 1 , 2 Injury occurs during late cocking and acceleration phases of throwing in such athletes as baseball pitchers. 1 The first reconstruction technique, performed by Dr. Frank Jobe, was made famous by notable Major League Baseball player Tommy John, who underwent the original “Tommy John” procedure to reconstruct his UCL in 1974. The UCL reconstruction allowed for a more successful career after surgery.…”
mentioning
confidence: 99%